2022
DOI: 10.3389/fnut.2022.849301
|View full text |Cite
|
Sign up to set email alerts
|

Host and Clostridioides difficile-Response Modulated by Micronutrients and Glutamine: An Overview

Abstract: Changes in intestinal microbiota are integral to development of Clostridioides difficile (C. difficile)—associated nosocomial diarrhea. Certain diets, especially Western diets, increase susceptibility to C. difficile infection (CDI). Here, we discuss recent findings regarding how nutrients modulate response of the host and C. difficile during infection. Calcium has a role in the sporulation and germination process. Selenium is effective in reducing the total amount of C. difficile toxin A (TcdA) and toxin B (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It has been reported that bile acids ( Tam et al, 2020 ), short-chain fatty acids ( Yuille et al, 2015 ), and the trace element selenium ( Loureiro et al, 2022 ) were considered potential inhibitors of TcdB-induced cytotoxicity, however the reports on fecal TcdB inhibitors are limited. Our study showed that significant differences in functional and toxical TcdB levels were observed between patients with CDC and CDI, while their total levels of TcdB protein were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bile acids ( Tam et al, 2020 ), short-chain fatty acids ( Yuille et al, 2015 ), and the trace element selenium ( Loureiro et al, 2022 ) were considered potential inhibitors of TcdB-induced cytotoxicity, however the reports on fecal TcdB inhibitors are limited. Our study showed that significant differences in functional and toxical TcdB levels were observed between patients with CDC and CDI, while their total levels of TcdB protein were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Loureiro et al [ 146 ] analyzed the modulation of response of host and C. difficile by nutrients, including Ca 2+ , that play a key role in sporulation and germination of C. difficile in the gut [ 146 ], reporting that there was only one recent paper describing a role of Ca 2+ in vitro [ 82 ] and that no reports on Ca 2+ uptake or serum Ca 2+ levels in CDI in patients or murine models.…”
Section: Alteration In Ca 2+ Homeostasis By Tcda A...mentioning
confidence: 99%